Coherently strained and dislocation‐free architectured AlGaN/GaN submicron‐sized structures. Issue 2 (17th July 2021) - Khalilian, Maryam; Persson, Axel; Lindgren, David; Rosén, Martin; Lenrick, Filip; Colvin, Jovana; Ohlsson, B. Jonas; Timm, Rainer; Wallenberg, Reine; Samuelson, Lars; Gustafsson, Anders
Abstract: To improve the performance and efficiency of Al containing III‐Nitride‐based devices, a number of issues must be addressed, especially the presence and generation of dislocations and other structural defects. The main sources of the dislocations are growth on non‐native substrates and heteroepitaxial growth of lattice‐mismatched layers. We demonstrate the ability to completely avoid structural defects including dislocations in Alx Ga1‐x N layers with x up to 0.90 and thicknesses over 100 nm, grown directly on submicron‐sized, flat‐topped GaN platelets. These structures have an excellent homogeneity over an entire array. The GaN platelets were produced by epitaxial growth and reformation of GaN nanowires, effectively blocking the propagation of threading dislocations (TDs) from the underlying substrate. The platelets have a sufficiently small volume to elastically accommodate the strain built up in the architectured AlGaN/GaN heterostructures. Effectively, we have designed a sacrificial nano‐scaled GaN seed, with the ability to be strained by the AlGaN layer grown on top of it. The conditions for the growth of the AlGaN are chosen to avoid the creation of misfit dislocations and other structural defects. These thick and structural defect‐free, submicron‐sized AlGaN/GaN structures may open up a new path for highly efficient electronic and optoelectronic devices. These structures can be used as substrates for light‐emitting diodes and transistors, either as individual devices or arrays in parallel, depending on the need for light output or transistor current. Abstract : We demonstrate dislocation free AlGaN/GaN heterostructures based on micron‐sized platelets seeded by nanowires grown from holes in a growth mask. Layers over 100 nm in thickness with an Al content of up to 90% are defect free and open a path to the fabrication of e.g. highly efficient UV‐LEDs, either as individual emitters, or arrays rivalling planar growth.